Consumer Behaviour Towards Passengers’ Cars: A Study in Meerut Region - Saharan, Mohit; Singhal, R. K (Journal of Commerce and Trade, 2018)
This paper explores the consumer behaviour towards passenger cars in Meerut region. The scope of the study is limited to certain important behavioural aspects like information search and evaluation, brand preference and brand loyalty and factors of motivation. Understanding the customer’s satisfaction of the product will help the automobile manufacturer in developing their products to meet customer’s needs and designing the proper marketing programs and strategy. Classification-JEL : L11, L22, P46